2019
DOI: 10.1111/jcmm.14123
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen‐related receptor alpha mediates chemotherapy resistance of osteosarcoma cells via regulation of ABCB1

Abstract: Chemotherapy resistance is one of the major challenges for the treatment of osteosarcoma ( OS ). The potential roles of oestrogenic signals in the chemoresistance of OS cells were investigated. As compare to the parental cells, the doxorubicin and cisplatin ( CDDP ) resistant OS cells had greater levels of oestrogen‐related receptors alpha ( ERR α). Targeted inhibition of ERR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…In addition, inhibition of ERRα could reverse its promoting effects and trigger programmed cell death and cellular cycle arrested in PC cells. Furthermore, recent studies imply that ERRα has been participating in chemoresistance of many tumors, more importantly, targeted inhibition of ERRα could restore chemosensitivity of those cancer cells [11][12][13][14]. Taken together, these findings indicated that ERRα might be a treatment target for PC.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, inhibition of ERRα could reverse its promoting effects and trigger programmed cell death and cellular cycle arrested in PC cells. Furthermore, recent studies imply that ERRα has been participating in chemoresistance of many tumors, more importantly, targeted inhibition of ERRα could restore chemosensitivity of those cancer cells [11][12][13][14]. Taken together, these findings indicated that ERRα might be a treatment target for PC.…”
Section: Introductionmentioning
confidence: 91%
“…Unluckily, only in few cases the snoRNA host genes are known, limiting the number of druggable targets. At preclinical level, several siRNA- or shRNA-based tools have successfully reversed Dox resistance in osteosarcoma, e.g., by directly silencing Pgp [ 59 , 60 ] or by silencing transcription factors, as estrogen-related receptor α (ERRα) that up-regulates Pgp [ 61 ] or nuclear factor (erythroid-derived 2)-like 2 (NRF2) that mediates resistance to oxidative stress and up-regulates multiple ABC transporters [ 62 ]. The major advantage of these approaches is that they can achieve high specificity in targeting a gene or a pathway involved in chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of ERRα in drug resistance has been widely studied in breast cancer and osteosarcoma (44)(45)(46)(47)(48). However, its role in PCa drug resistance was rarely examined.…”
Section: Discussionmentioning
confidence: 99%